Enhancing service quality improvement strategies by integrating Kano's model with importance-performance analysis. (19th August 2011) - Lin, Shu-Ping; Chan, Ya-Hui
In resources limited situation, seeking effective ways to fulfil customers' needs is fundamental for the success of a business in the long-term. Importance-performance analysis (IPA) and Kano's model are two main decision making techniques for improving customer satisfaction. This study aims at developing a strategic action model by integrating Kano's model with IPA to consider the phenomena of non-linear relationship between attribute performance and overall satisfaction. To verify the validity of this integrated model, a Taiwanese online job agency case is then presented. The results show that this integrated model can certainly advance service quality improvement strategies according to different contributions of diverse quality factors on customer satisfaction. Thus, the new proposed strategic action model can be regarded as a comprehensive tool to help managers make effective strategies to enhance customer satisfaction.